2017
DOI: 10.1007/s11336-017-9579-4
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian Estimation of the DINA Q matrix

Abstract: Cognitive diagnosis models are partially ordered latent class models and are used to classify students into skill mastery profiles. The deterministic inputs, noisy "and" gate model (DINA) is a popular psychometric model for cognitive diagnosis. Application of the DINA model requires content expert knowledge of a Q matrix, which maps the attributes or skills needed to master a collection of items. Misspecification of Q has been shown to yield biased diagnostic classifications. We propose a Bayesian framework fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
88
0
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(92 citation statements)
references
References 32 publications
3
88
0
1
Order By: Relevance
“…It was found that attributes defined in the Q matrix did not contain the information about the degree of complexity of the objects. In the future, we will further validate this Q matrix using many recent techniques in psychometrics (e.g., Chen et al, 2018a). Bolshakova, N., and Azuaje, F. (2003).…”
Section: Discussionmentioning
confidence: 99%
“…It was found that attributes defined in the Q matrix did not contain the information about the degree of complexity of the objects. In the future, we will further validate this Q matrix using many recent techniques in psychometrics (e.g., Chen et al, 2018a). Bolshakova, N., and Azuaje, F. (2003).…”
Section: Discussionmentioning
confidence: 99%
“…For the estimation of the RSDM, we used priors of N(0, 20) for each item parameter and Dirichlet(2) for each attribute profile, similar to Liu and Jiang (2018). These priors are considered less informative and have been recommended in similar DCM studies, such as Chen, Culpepper, Chen, and Douglas (2018) and Jiang and Carter (2018). For the model constraints, we successfully implemented the first constraint as described in the model.…”
Section: Discussionmentioning
confidence: 99%
“…iii The author do, however, note that this Q-matrix has been suggested to be revised by some previous studies (e.g., Chen, Culpepper, Chen & Douglas, 2018). But it is still fair to compare several models with the same Q-matrix, especially when there is no definite conclusion about the revision of this Q-matrix.…”
mentioning
confidence: 90%